Academic experience of international students on scholarships in Malaysian universities : the case of a private university college. - Olutokunbo, Adekalu Samuel; Ismail, Ismi Arif; Suandi, Turiman (Macrothink Institute, 2013)
The rate at which most organizations and institutions of learning offer scholarship and grant to attract international students is becoming competitive among citizens of the developing nations who seek to gain international education experience for better career opportunities and educational development. At present, Malaysia is fast becoming an educational centre for international students as the country has set a target by year 2020 to attract 200,000 international students from Africa, Asia and the Middle East and other continents of the world. It then becomes imperative to investigate the readiness of the country in terms of the provisions in place for achieving this laudable goal. It is with this intent that this study investigates the academic experience of international students on scholarships in Malaysian Universities. An in-depth interview was conducted among a group of international students in Malaysia with a particular focus on Petroleum Technology Development Fund (PTDF) scholarship recipients studying at a Private University College. The study revealed that, the scholars are generally satisfied and able to cope with the classroom teaching as well as academic huddles at Linton University College (LUC) while adapting to host challenges. They are able to comply with renewal of students’ visa regulations in Malaysia. This study suggested among other things, an initiative such as recommendation to improve international student academic experience studying in Malaysian Universities with an effort to enhance their academic performance and career opportunities, when the scholars returned to their respective countries.